PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PT. BANK MANDIRI (PERSERO) TBK, BRANCH PANGKALAN BRANDAN - Adriana Febelastika Sitompu; Aldwin Surya; Anton A. P Sinaga (Jurnal Darma Agung, 2021)
This study aims to determine: the direct influence of work discipline organizational culture and work motivation on the performance of PT. Bank Mandiri (Persero) Tbk, Branch Pangkalan Brandan, totaling 76 employees. The data collection techniques of this study were questionnaires and observations. While the data analysis technique used is the classical assumption test, multiple regression F test t test and the coefficient of determination. The results of testing the coefficient of determination or R2 obtained Adjusted R Square value of 0.445, meaning that the variables of Organizational Culture, Work Discipline, Work Motivation are able to explain how the Employee Performance at PT. Bank Mandiri (Persero) Tbk, Branch Pangkalan Brandan amounted to 44.5%. While the remaining 55.5% by other factors not examined in this study such as leadership style, job satisfaction, work environment, personal abilities, work climate and other socio-economic factors.